TRANSFORMATIONAL LEADERSHIP TOWARDS TEACHER PERFORMANCE - Salma, Durotun Napisah; Abdurakhman, Omon; Hayu, Wiworo Retnadi Rias (Universitas Djuanda, 2016)
The high teacher’s performance can be affected by a leader (principal), because the leader can direct and guide to control his subordinates. Observationally, an elementary school in Cigudeg district tend to use a transformational leadership style. This type of research is quantitative based on regression analysis. The subjects of this research is teachers in SDN Cikawung 01 and SDN Ciangger 03, Cigudeg. Technique of the collecting data in this research use observation and questionnaires. Based on the analysis of the questionnaire data by using t test, it is found that tcount = 2,62 > ttable = 2,46 so it can conclude that there are influence of transformational leadership towards teacher’s performance. Furthermore, based on the result of calculation of correlation coefficient between transformational leadership and the teacher performance obtained value of r= 0,604, meaning that there are strong effect between transformational leadership with teacher performance. Therefore, it can conclude that better the transformational leadership then increasing the performance of the teachers at SDN Cikawung 01 and SDN Ciangger 03 Cigudeg, Bogor.